Ultrasound as a Sole Modality for Prenatal Diagnosis of Placenta Accreta Spectrum: Potentialities and Pitfalls - Gulati, Anshika; Anand, Rama; Aggarwal, Kiran; Agarwal, Shilpi; Tomer, Shaili (Indian Journal of Radiology and Imaging, 2021)
Background Placenta accreta spectrum (PAS) is a significant cause of maternal and neonatal mortality and morbidity. Its prevalence has been rising considerably, primarily due to the increasing rate of primary and repeat cesarean sections. Accurate prenatal identification of PAS allows optimal management because the timing of delivery, availability of blood products, and recruitment of skilled anesthesia, and surgical team can be arranged in advance.Aims and Objectives This study aimed to (1) study the ultrasound and color Doppler features of PAS, (2) correlate imaging findings with clinical and per-operative/histopathological findings, and (3) evaluate the accuracy of ultrasound for the diagnosis of PAS in patients with previous cesarean section.Materials and Methods This prospective study was conducted in radiology department of a tertiary care hospital. After screening 1,200 pregnant patients, 50 patients of placenta previa with period of gestation ≥ 24 weeks and history of at least one prior cesarean section were included in the study. Following imaging features were evaluated: (1) gray scale covering intraplacental lacunae, disruption of uterovesical interface, myometrial thinning, loss of retroplacental clear space, and focal exophytic masses; and (2) color Doppler covering intraplacental lacunar flow, hypervascularity of uterine serosa–bladder wall interface, and perpendicular bridging vessels between placenta and myometrium.Study Design Present study is a prospective one in a tertiary care hospital.Results Of the 19 PAS cases, 18 were correctly diagnosed on ultrasonography (USG) and confirmed either by histopathological analysis of hysterectomy specimen or per-operatively due to difficulty in placental removal. PAS was correctly ruled out in 27 of 31 patients. The diagnostic accuracy of USG was 90%. The sensitivity, specificity, positive, and negative predictive values were 94.7, 87.1, 81.8, and 96.4%, respectively.Conclusion Ultrasound is indispensable for the evaluation of pregnant patients. It is an important tool for diagnosing PAS, thereby making the operating team more cautious and better equipped for difficult surgery and critical postoperative care. It can be relied upon as the sole modality to accurately rule out PAS in negative patients, thereby obviating unnecessary psychological stress among patients due to possible hysterectomy.
Keywords: antepartum hemorrhage; cesarean; Doppler; hysterectomy; maternal mortality; morbidly adherent placenta; placenta accrete; placenta increta; placenta percreta; placental lacunae